Validation of an Inventory of Sensitivity to Ideological Radicalization (ISIR-14) in a Mexican Sample - Julio C. Penagos-Corzo; Isabel Govela (Social Sciences)
The development and validation of the Ideological Radicalization Sensitivity Inventory (ISIR-14) in a Mexican sample is presented. A total of 537 participants were assessed. Exploratory and confirmatory factor analyses supported a five-factor structure that explained 53.7% of the variance, with excellent model fit indices (CFI = 0.985, TLI = 0.978, RMSEA = 0.033). Evidence of concurrent validity was suggested through significant correlations with the Emotional Response to Unfairness Scale (ERU) and the Exposure to Violent Extremism Scale (EXPO-12). Reliability analyses indicated good internal consistency (ω = 0.819) for the instrument. Additionally, temporal stability, analyzed in a second study with 171 participants, showed moderate stability (r = 0.601). The study aimed to test the hypothesis that sensitivity to ideological radicalization can be reliably measured through a multidimensional instrument aligned with theoretically derived psychological risk factors, namely, inclination to seek redress, perceived social disconnection, ideological superiority, exposure to extreme ideologies, and collective/group identity. The results suggest that the ISIR-14 is a reliable and valid tool for assessing sensitivity to ideological radicalization. The scale provides a foundation for future research and interventions aimed at identifying and addressing factors associated with radicalization processes.